Impacts of high-sucrose diet on circadian rhythms in the small intestine of rats. (3rd June 2019) - Sun, Shumin; Hanzawa, Fumiaki; Umeki, Miki; Matsuyama, Yasuko; Nishimura, Naomichi; Ikeda, Saiko; Mochizuki, Satoshi; Oda, Hiroaki
ABSTRACT: Excessive sucrose intake, known as fructose toxicity, leads to fatty liver, hyperlipidemia, and metabolic syndrome. Circadian disorders also contribute to metabolic syndrome. Here, we investigated the effect of excessive sucrose intake on circadian rhythms of the small intestine, the main location of sucrose absorption, to elucidate a mechanism of sucrose-induced abnormal lipid metabolism. Male Wistar rats were fed control starch or high-sucrose diets for 4 weeks. High-sucrose diet-induced fatty liver and hypertriglyceridemia in rats. Amplitudes of PER1/2 expression oscillations in the small intestine were reduced by excessive sucrose, while gene expression of GLUT5 and gluconeogenic enzymes was enhanced. These changes would contribute to interfering in lipid homeostasis as well as adaptive responses to control fructose toxicity in rats.